Field Researchers preparing for the launch of Al Chartier - Bazely, Dawn (1983)
Two field researchers are seen working on the Al Chartier in preparation for its launch. Branded on the side of the Al Chartier is a Churchill logo. Churchill was the location of Camp Finney